2014
DOI: 10.5935/paet.v7.n1.11
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the gene flow between transgenic and non transgenic soybean cultivars

Abstract: The objective of this study was to assess and quantify the gene flow in soybean. It were used two batches of soybean seeds, the cultivar CD 201 (non transgenic) and the CD 212 RR (transgenic, with the RR gene), both from the breeding program of COODETEC (Cooperativa Central de Pesquisa Agricola), located in Cascavel (Paraná State-Brazil). They were sown in an experimental design of concentric rings, totalizing an area of 100 m of diameter and 2.500 m 2 . The sampling points were delimited in eight halfway rays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Current studies on gene flow from transgenic to nontransgenic crop cultivars aim to gain information on how to prevent inadvertent admixture of those crops through outcrossing. A few studies have reported gene flow from transgenic soybean to non-transgenic soybean cultivars in the fields of Brazil [20][21][22][23], China [24][25][26][27][28], Japan [29], and Korea [30,31]. These studies mostly used herbicideresistant transgenic soybean as pollen donors and measured the rates of gene flow and the distance at which gene flow can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on gene flow from transgenic to nontransgenic crop cultivars aim to gain information on how to prevent inadvertent admixture of those crops through outcrossing. A few studies have reported gene flow from transgenic soybean to non-transgenic soybean cultivars in the fields of Brazil [20][21][22][23], China [24][25][26][27][28], Japan [29], and Korea [30,31]. These studies mostly used herbicideresistant transgenic soybean as pollen donors and measured the rates of gene flow and the distance at which gene flow can occur.…”
Section: Introductionmentioning
confidence: 99%